Changes in the weapons tactics of the Polish knighthood in the first half of the 15th century - Teodorczyk, Jerzy (Balcanica Posnaniensia. Acta et studia, 1997)
The article analyses transformations in the armament and tactics of the Polish knighthood in the first half of the fifteenth century in the context of the Ottoman threat and changes taking place in European warfare. The research problem concerns the reasons for the superiority of Ottoman forces over Christian armies and the ways in which the Polish knighthood adapted to new military realities. The aim of the study is to present the evolution of Polish weaponry and tactics and to evaluate the effectiveness of the reforms introduced. The author draws upon findings from military archaeology, the study of arms and armour, and analyses of historical sources concerning military equipment and army organization. The article demonstrates that Ottoman armies possessed an advantage thanks to their mobile cavalry, the use of composite bows, and disciplined Janissary infantry fighting in compact formations. European knighthood, based on loose lancer formations, was unprepared to fight an opponent employing rapid manoeuvres and the tactic of feigned retreat. During the reign of Władysław II Jagiełło, reforms were initiated in Poland that included the development of mounted crossbow units and infantry modelled on Hussite troops. The author also points to eastern influences visible in the armament of the Masovian and Lithuanian knighthood. The results of the analysis indicate that adapting Polish military art to the Ottoman threat was a gradual but necessary process for maintaining the state’s military effectiveness.